Tempo, 1996 - Texas Association for the Gifted and Talented, Austin; Sayler, Michael; Texas Association for the Gifted and Talented, Austin ([S.l.] : Distributed by ERIC Clearinghouse, 1996)
This document consists of the four issues of "Tempo," the newsletter of the Texas Association for the Gifted and Talented (TAGT), published during 1996. Each issue focuses on a specific theme, such as math and science instruction, culturally diverse gifted students, parents and teachers working together, and future challenges. Articles include: "Science Education for Gifted Students" (Joyce VanTassel-Baska); "Young Math Whizzes: Can Their Needs Be Met in the Regular Classroom?" (Ann Lupkowski-Shoplik); "Nurturing Future Edisons: Teaching Invention to Gifted Students" (Jonathan Plucker and Michael E. Gorman); "Recruiting and Retaining Diverse Students in Gifted Education" (Donna Y. Ford and J. John Harris); "Hispanic and Gifted/Talented: Can You Be Both?" (Rebecca V. Rendon); "The Education of a Gifted Non-English Speaking Immigrant" (Becky Alanis); "Discovering and Nurturing Talents in Young Hispanic Students" (Marta Mountjoy); "Alternate Identification for Gifted African-Americans" (Donna Ashby); "Thinking about the September Challenge" (Donna Enersen), which discusses parents and teachers working together; "Advocating for Appropriate Education for Your Child" (Colleen Elam); "A Taste of Gifted and Talented for Parents" (Elma Torres); "Texas Law and Parent Rights and Responsibilities" (Ann Wink); "A Thoughtful Look at the Concept of Talent Development" (Francoys Gagne); "There and Back Again: Searching the Past for Future Answers" (Michael W. Cannon); "Magnet Programs for Gifted Girls: A Parent's Perspective" (Ava Welge and Beth Fouse); and "Home Schooling Gifted Children: The Ultimate Pullout Program" (Brooke Randal). Some articles include references. (CR)
Availability: Dr. Michael Sayler, University of North Texas, P.O. Box 13857, Denton, TX 76203-6857; fax: 817-565-2089; telephone: 817-565-4699.
ERIC Note: For each of the four serial issues analyzed separately under their respective theme titles, see EC 305 192-195.
Tempo, v16 n1-4 1996.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Ability Identification; Black Students; Child Advocacy; Cultural Differences; Educational Legislation; Educational Strategies; Elementary Secondary Education; Gifted; Hispanic Americans; Home Schooling; Inventions; Language Minorities; Magnet Schools; Mathematics Education; Minority Group Children; Parent Rights; Parent School Relationship; Science Education; Student Development; Talent; Talent Development; African Americans -- Texas; Collected Works, Serials; Guides, Non-Classroom.; Reports, Descriptive